Identifying children at risk: Empowering teachers using the RedFlag app - Franzina Coutinho; Gauri Saxena; Sonali Saini (International Journal of Educational Research Open, 2022)
The present study evaluates a teacher training program that utilises an app-based screening tool to empower teachers to correctly identify children ‘at-risk’ for various developmental disabilities, mental health challenges and demographic challenges. A pre-post research design was used to assess the effectiveness for screening these risks with 1061 teachers who were recruited from three districts in Tamil Nadu, India. The teachers were asked to assess three case studies representative of children at -risk. Data collection was via software (Google forms) pretest. They were then trained in using the RedFlag App and were asked to reassess the same three case studies for likelihood of risk using the App. Results indicated a significant increase in the likelihood of correct assessment while using the RedFlag App (OR = 2,689, 95%, CI: 1.80–4.00). The improvements were significant across multiple demographic factors including age of teachers, area of residence, and gender. The implications of the findings are discussed.